Comparison of neural networks for solving the travelling salesman problem - La Maire, B. F. J.; Mladenov, V. M. (2012 11th Symposium on Neural Network Applications in Electrical Engineering, 2012)
The TSP deals with finding a shortest path through a number of cities. This seemingly simple problem is hard to solve because of the amount of possible solutions. Which is why methods that give a good suboptimal solution in a reasonable time are generally used. In this paper three methods were compared with respect to quality of solution and ease of finding correct parameters: the Integer Linear Programming method, the Hopfield Neural Network, and the Kohonen Self Organizing Feature Map Neural Network.